Development of 5S practice checklist for manufacturing industry - Khamis, N.; Ab. Rahman, M. N.; Jamaludin, K. R.; Ismail, A. R.; Ghani, J. A.; Zulkifli, R. (International Association of Engineers, 2009)
This paper explores the practical use of the 5S Checklist for environment, housekeeping and health, as well as safety improvement purposes at two manufacturing organizations. The main objective of this study is to assess the implementation of 5S and development of the 5S Activity Checklist in manufacturing companies. The scope for this study covers the following areas: identifying problems, looking into critical success factors, their outcomes and recommendations. In addition, factors that may act as constraints to the implementation of the 5S activity and possible solutions for the industries are also identified through observation and evaluation of the improved environmental performance. The study is conducted using a systematic approach with specific software in order to get the most accurate results. In conclusion, effective implementation of the 5S activity depends on the commitment of the top level management, total involvement of the staff at all levels within the company, function and background of the business, publicity given to the 5S activity and finally the training conducted for the organisation in implementing the 5S practices.